Hubungan Antara Tingkat Kecemasan Komunikasi Dan Konsep Diri Dengan Kemampuan Penyesuaian Diri - ., Muchibuddin; Rahardjo, Turnomo (Interaksi Online, 2021)
Adjustment is an important thing for every individual, including a student. Student data from the Nurul Hikmah Islamic Boarding School (PPMNH) shows that there are students who leave before completing their education at the pesantren. This is due to the low adjustment ability of PPMNH students. This study aims to determine the relationship between the level of communication anxiety and self-concept with the students’ adaptability. This research uses quantitative methods. The population of this study were students of the PPMNH in 2019. The sample was determined using a random sampling technique and a total sample of 98 people was obtained. The theories used in this study are Uncertainty Reduction Theory (URT) and Anxiety Uncertainty Management (AUM) Theory. The results show that the level of communication apprehension has negative correlation with students’ adapability and self-concept has positive correlation with students’ adaptability. Student’s adaptability will increases when the level of communication apprehension is lower and self-concept is higher.